2019
DOI: 10.1123/ijsc.2018-0173
|View full text |Cite
|
Sign up to set email alerts
|

International Sport Federations’ Social Media Communication: A Content Analysis of FIFA’s Twitter Account

Abstract: This study aims to analyze the way in which Twitter is used by international sport federations to interact and engage with its followers. A content analysis of 5,389 online messages tweeted by FIFA using NVivo qualitative data analysis software was conducted between August 2014 to January 2015. Results suggest that FIFA does not use Twitter to its full potential by mainly sharing one-way information rather than engaging to a greater level with its followers. The research highlights the importance of the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
1
16
0
3
Order By: Relevance
“…Several PTSOs have started taking social responsibility initiatives as a means of managing, organizing, and controlling the nonsporting dimensions of soccer (Pedersen & Rosati, 2019). PTSOs do view such actions as an opportunity to strengthen their reputation and build trust among their community (Winand, Belot, Merten, & Kolyperas, 2019). It is difficult to think of any other moment in the modern era of sport when PTSOs could do just that.…”
Section: A Brief Backgroundmentioning
confidence: 99%
“…Several PTSOs have started taking social responsibility initiatives as a means of managing, organizing, and controlling the nonsporting dimensions of soccer (Pedersen & Rosati, 2019). PTSOs do view such actions as an opportunity to strengthen their reputation and build trust among their community (Winand, Belot, Merten, & Kolyperas, 2019). It is difficult to think of any other moment in the modern era of sport when PTSOs could do just that.…”
Section: A Brief Backgroundmentioning
confidence: 99%
“…A lo largo de los años, la gestión de estas plataformas digitales por parte de las organizaciones deportivas han sido objeto de estudio. Desde equipos y clubes deportivos (ACHEN, 2019;JORDAN;UPRIGHT;FORSYTHE, 2017;MACHADO et al, 2020; a federaciones internacionales (BURSON COHN & WOLFE SPORTS, 2021;GINESTA, 2009;VILANOVA, 2009;WINAND et al, 2019) o incluso deportistas (HAYES, 2020;SHARPE;MOUNTIFIELD;FILO, 2020;WITKEMPER;LIM;WALDBURGER, 2012).…”
Section: Enfoques De Gestión En La Comunicación Digital En Las Organi...unclassified
“…They revealed four types of communication that were often used to engage fans: informing (e.g., news), marketing (e.g., promotion, sales), personalising (e.g., initial contact, direct response) and activating (e.g., group involvement, gathering feedback). Winard et al (2018) analysed content from FIFA's Twitter account and revealed that FIFA did not fully utilise the potential of Twitter as a channel of communication with football fans.…”
Section: Content Analysis In Sportsmentioning
confidence: 99%
“…group involvement, gathering feedback). Winard et al (2018) analysed content from FIFA’s Twitter account and revealed that FIFA did not fully use the potential of Twitter as a channel of communication with football fans.…”
Section: Related Literaturementioning
confidence: 99%